The Visual Reception of Parajanov in Italy. Poetry, Fairytale and Icon - Perfetti, Filippo (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The contribution analyzes the visual reception of Sergey Parajanov’s work in Italy, summarizing his presence from the 1960s to the 1990s at film festivals and his subsequent recognition through Italian television, particularly thanks to Enrico Ghezzi. It then illustrates how Parajanov has been viewed through the lenses of “poetry cinema” and folkloric-fairy tale elements, themes that resonate in both Soviet and Italian criticism. Հոդվածում քննարկվում է Սերգեյ Փարաջանովի ստեղծագործության տեսողական ընկալումն Իտալիայում։ Հիմք են ծառայել թե՛ 1960-1990-ական թվականներին անցկացված կինոփառատոներում ռեժիսորի ներկայությունը, և թե՛ իտալական հեռուստատեսության շնորհիվ (ի մասնավորի՝ Էնրիկո Գեցցիի ջանքերով) երկրում նրա հետագա ճանաչումը լուսաբանող նյութերը։ Целью статьи является анализ зрительного восприятия творчества Сергея Параджанова в Италии. Использовались материалы, освещающие его присутствие в 1960-1990-ых годах на кинофестивалях, как и дальнейшее его признание в стране благодаря итальянскому телевидению при посредстве, в частности, Энрико Гецци.
Keywords: Sergey Parajanov; Cinematography